Growth, antioxidant activity and volatile compounds of lemon basil (Ocimum citriodorum Vis.) affected by led irradiance, nutrient concentration and postharvest stroge. - Mat Daud, Zurafni (2020)
In this study, the effects of irradiance levels of LEDs of red and blue spectra, EC of nutrient solution, and nitrogen concentration on growth performance, yield productions, phytochemical contents (antioxidant activity), and volatile compounds of lemon basil (Ocimum citriodorum Vis.) were investigated. A lightemitting diode (LEDs) has tremendous potential as a sole-source lighting system for crop production in a controlledenvironment facility. Their small size, long operating lifetime, durability, wavelength specificity, and relatively cool emitting surfaces make these solid-state light sources idealfor use in the plant lighting system. The objective of this study was to examine the effectsof varying irradiance levels of LEDs with red and blue spectra (4 to 1 ratio) on the growth performance, yield productions, and phytochemical contents (antioxidant activity) of lemon basil (Ocimum citriodorum Vis.) in a controlled environment facility. The effect of varying irradiance levels of LEDs of red and blue spectra on plant growth can be seen on 12 days after planting and beyond. Similar trends of responses were also seen in the plant canopy, leaf number, and leaf area. Differences in all parameters measured were significant as the plant growth advanced. The fresh weight of leaves, stem, and roots were markedly affected by the treatments. Moreover, lemon basil cultivated at irradiance levels of LEDs with red and blue spectra at 160 μmol m-2 s-1 also contributed to more significant quality attributes such as chlorophyll a, total chlorophyll,carotenoid contents, total flavonoid contents, and total phenolic contents as well as an individual phenolic compound such as rosmarinic acid and gentisic acid, but lower in nitrate content as compared with other irradiance levels. Data generated from this study revealed that LEDs of red and blue spectra at irradiance level of 160 μmol m-2 s 1 could be used effectively as an artificial light source for the lemon basil production under controlled environmental conditions. In the subsequent study, the effects of different irradiance levels of LEDs of red and blue spectra and electrical conductivity of the nutrient solution and nitrogen concentrations on the growth performances, yield productions and phytochemical contents (antioxidant activities) and volatile compounds were determined. The results indicated that the high irradiance levels of LEDs of red and blue spectra at 160 μmol m-2 s-1 and moderate electrical conductivity of nutrient solution at 2.6 mS cm-1 and nitrogen concentrations at mg L-1 contributed to better growth performance (plat height, canopy diameter, and the number of leaves), higher yield production and quality attributes as well as carotenoid contents, total flavonoid, and total phenolic contents as well as caftaric acid concentration. The postharvest quality of lemon basil (Ocimum citriodorum Vis.) stored under different storage temperature at different storage period that cultivated under different irradiance levels of LEDs of red and blue spectra was studied. The results demonstrated that irradiance levels of LEDs, storage temperature, and storage period affected the total flavonoid contents, total phenolic contents, and antioxidant activity of lemon basil. Increasing temperature and irradiance levels of LEDs increased total flavonoid and total phenolic contents, and antioxidant activity of lemon basil. Storage temperature at 5˚C was better in retaining total flavonoid contents and antioxidant activity, while storage temperature at 15˚C was better in the retention of phenolic compounds concentration of caftaric and rosmarinic acid. Overall, the present study’s findings have improved our understanding of the effects of irradiance levels of LEDs of the red and blue spectra, the electrical conductivity of the nutrient solution, and nitrogen concentrations and their interaction on lemon basil plants. Besides, this is beneficial for optimizing irradiance levels and electrical conductivity of the nutrient solution and nitrogen concentrations to enhance crop production and quality. In addition, the storage temperature also crucial for better postharvest quality attributes.